Factors associated with maintenance of breastfeeding and early weaning in children under 2 years (Research, Society and Development, 2020)
The presente paper of conclusion (TCC) delas with Breastfeeding (BF).  The Breast Mil kis Recognized as the most suitable and complete food for childreen uo to the first six months of age. Objective: To identify the Factors associated with the maintenance of breastfeeding and early weaning in children under 2 years old. The study had a quantitative approach, numerically pointing out the frequency and intensity of the behavior of individuals in a certain group. Method: Quantitative study of exploratory and descriptive type. Conclusion: When analysing the data on the factors associated with early weaning it is notable that there is a significant association between the child’s age and breastfeeding, that is, there is a statistically positive relationship between the fact that the child is less than 6 months old and still breastfeed exclusively, meeting what is recommended by health agencies.